The Influence of Sales Growth, Asset Structure, Profitability, and Business Risk on Capital Structure - Pratiwi, Diah; Maharani, Betari; Afif, Naufal (Islamic Micro Finance Journal, 2024)
Capital structure is the proportion of a company's finances between internal and external sources of funds as financing a company and as a determinant of the amount of debt for funding the company's operations. The higher use of debt in the capital structure can increase installments and interest payments that become business obligations and can result in the risk of cash flow not being fulfilled, resulting in a decrease in stock prices and the bankruptcy of the company. This study aims to examine the effect of sales growth, asset structure, profitability, and business risk on capital structure. The data used in this study are secondary. The population of this study is made up of basic industrial and chemical companies listed on the IDX in 2017–2022. The sampling technique used in this study was the purposive sampling method. The sample selected was 19 companies through predetermined criteria. Test the hypothesis in this study using multiple linear regression analysis. The results of this study show that sales growth does not affect the capital structure. Asset structure has a positive effect on capital structure. Profitability negatively affects the capital structure. Business risk does not affect the capital structure